Comparing the effect of MTC1 gene variation on hospitalization speed in terms of the lactic threshold of handball players - Majeed Saeed , Wajdi; Hadi Jasim , Mohamed; Ahmed , aif Saad; Ahmed, Omar Saad (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the genetic diversity of the MCT1 gene and the speed of hospitalization for handball players. Besides, comparing the genetic diversity and its effect on the speed of hospitalization in terms of the lactic threshold. The research problem is to question what level has the most influence on the speed of hospitalization in terms of the lactic threshold for handball players. Therefore, the researcher assumed that there were statistically significant differences between the levels of the MCT1 gene among handball players. The researcher used the descriptive method in the survey due to its relevance to the research problem. The community was chosen in an intentional style, and they are the Diwaniyah youth handball players team 2017-2018 year, and they are (twelve) players. The sample was divided according to the levels of the MCT1 gene as the high level reached was five players. The average level is four. The number of the low level reached was three players. The exploratory experiment was conducted on (Tuesday) on (19/1/2018) in the sports hall of the Diwaniyah Sports Club. The experiment carried out on a sample consisting of (4) players and the scientific foundations of the test performed. The main experiment conducted between Monday 5/2/2018 to 2/8/2018, during which the hospitalization of the lactic acid concentration measured to find out the effectiveness of the MCT1 gene. By training on the physical exertion bike for 30 seconds, according to Bruce's test and repetition, the training set twice with a rest for 60 seconds between them. At the end of the effort, these measurements are obtained by continuing the work of the devices and measuring the concentration of lactic acid during (5, 10, 15, 20, 30, 60) minutes, and accordingly, three players tested for each day for four days after which the researcher collected and processed the data statistically.